Preliminary Phytochemical Tests and Antioxidant Potential of Catharanthus Roseus Extracts - Ethalsha, P.; Prema Kumari, P.; Mercy Salima, K. (Asian Journal of Engineering and Applied Technology, 2015)
Periwinkle (nayantara) is the common name for a pair of perennial flowering shrubs belonging to the Apocynaceae family. The herb has been used for centuries to treat a variety of ailments and was a favourite ingredient of magical charms it was in the middle ages. The latin name for this herb is Catharanthusroseus, but it was classified as Vincarosea, and is still called by that name in some of the herbal literature. The present study explores the various phytochemicals present in the plant so as to substantiate its antioxidant property and also shows the several phytoconstituents that contribute to its various medicinal properties. Preliminary phytochemical screening of the crude extracts revealed the presence of alkaloids,flavanoids, tannins, saponins and phenolics. During DPPH assay of methanol extract of aerial part of Catharanthusroseusshows highest antioxidant activity of 92.04% in 200(μg/ml). The results confirm that aerial part of Catharanthusroseuscan be used as source of drugs to fight infections caused by susceptible bacteria.